Salicornia ramosissima J. Woods seeds affected the normal regenerative function on carbon tetrachloride-induced liver and kidney injury - Ferreira, Daniela (2018)
The growing importance of Salicornia plants as bioactive agents and health promoters associated with the continuous demand for alternative treatments for liver disorders, has stimulated us to evaluate the renal and hepatic effects of S. ramosissima seeds in mice under normal conditions and exposure to toxic products as carbon tetrachloride (CCl4). Thus, histopathological and lipid peroxidation evaluations of the liver and kidneys were performed. Powdered dried seeds of S. ramosissima (SRS) were administered orally for 22 days at a dose of 2000 mg/kg/day to male mice in three different settings: 1) seed effects, 2) protection against CCl4 acute toxicity (0.2 mL/kg) and 3) regeneration after acute exposure to CCl4 (0.2 mL/kg), each study being performed with appropriate control animals. Mice treated with SRS per se had slightly enlarged hepatic sinusoids and noticeable renal inflammation. SRS did not show effective protection against mice exposed to CCl4 and had no positive influence on liver and kidney recovery after CCl4 administration. These results demonstrated that SRS failed to improve hepato- and nephrotoxicity, in addition to the apparent synergism between CCl4 and SRS under these experimental conditions. Although the biological mechanisms of S. ramosissima are not fully understood, the evidence suggests further research to elucidate its adverse biological effects.